A fault tolerant sensorless position estimation scheme for switched reluctance motor at low speed. Issue 4 (11th May 2020) - Dong, Feng; Chen, Hao; Xu, Shuai; Cui, Sihang
Abstract : Purpose: This paper aims to present a novel position sensorless control scheme with fault-tolerance ability for switched reluctance motor at low speed. Design/methodology/approach: First, the detection pulses are injected in the freewheeling and idle intervals of each phase. Second, the aligned position of each phase can be detected by comparing the consecutive rise time of detection current. Third, the whole-region rotor position and real-time rotational speed can be updated four times for the improvement of detection accuracy. Finally, the fault-tolerant control strategy is performed to enhance the robustness and reliability of proposed sensorless scheme under faulty conditions. Findings: Based on proposed sensorless control strategy, the estimated rotor position is in good agreement with the actual rotor position and the maximum rotor position error is 1.5°. Meanwhile, the proposed sensorless scheme is still effective when the motor with multiphase loss and the maximum rotor position error is 1.9°. Moreover, the accuracy of the rotor position estimation can be ensured even if the motor is in an accelerated state or decelerated state. Originality/value: The proposed sensorless method does not require extensive memory, complicated computation and prior knowledge of the electromagnetic properties of the motor, which is easy to implement. Furthermore, it is suitable for different control strategies at low speed without negative torque generation.